SKILLED AND UNSKILLED LOCAL AND FOREIGN LABOUR AS DETERMINANTS OF LABOUR PRODUCTIVITY IN MALAYSIA: A LONG-RUN FMOLS ANALYSIS - Mohammad Nor, Saffiah; Sahudin, Zahariah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Labour productivity is a contributing factor of economic growth, which reflects the efficiency of utilising workforce and production inputs by the economy. The constant gaps of productivity across industries in Malaysia have increased some issues concerning the roles of capital accumulation, labour composition, and intermediate input efficiency. This study examines the long-term relationship between labour productivity and labour composition, emphasising on skilled and unskilled local and foreign labour throughout major Malaysian industries, comprising agriculture, manufacturing, construction, along with accommodation and food services. The analysis adopts the Fully Modified Ordinary Least Squares (FMOLS) estimation technique to correct endogeneity and serial correlation in cointegrated panel models by using annual panel data from 2010 to 2021, thus providing robust long-run flexibility estimates. Empiric findings shows that intermediate inputs and capital are the primary factors of long-term labour productivity, where intermediate inputs significantly having positive impacts. Conversely, incompetent domestic workers significantly reduce productivity, resulting in the reduction of marginal returns, whereas competent domestic workers contributed significantly to the technical skills sectors such as manufacturing. Meanwhile, competent and incompetent immigrant workers show inadequate accumulated productivity impacts, signifying low spillovers and less absorption capacity. On the other hand, salary has no significant long-term impact on productivity, suggesting the lack of a strong wage-efficient mechanism. All in all, the findings revealed that Malaysia’s long-term productivity growth is predominantly driven by capital accumulation and efficient intermediate input, consistent with the conservative production theory and the Solow growth framework. Policy implications are corresponded to Malaysia’s Shared Prosperity Vision 2030 that focus on upgrading skills, organisational transformation, and innovation-driven investment to achieve sustainable productivity-led growth.